Develop a cost model to evaluate the economic benefit of remanufacturing based on specific technique - Yuchun Xu; Wei Feng (Journal of Remanufacturing, 2014)
Remanufacturing is a process of recovering used products to a like-new condition. It can potentially achieve considerable economic, environmental and social benefits in many applications. However, its economic benefit varies for different products and remanufacturing processes. This research aims to develop a framework and cost model to quantitatively evaluate the benefits of remanufacturing techniques to assist the decision making on end-of-life strategies. Additive manufacturing-based remanufacturing process has been modelled first, then cost breakdown structure for the process has been created, and the cost model has been developed. Validation of the cost model has been conducted based on expert judgement, and a case study has been carried out by using the developed cost model to compare the benefit of remanufacturing a specified component or making a new one.
Keywords: 650; End of life; Remanufacturing; Product recovery; Cost estimation; Cost engineering; Economic benefit analysis